أثر القواعد الفقهية في تأصيل فتاوى وبيانات اللجنة الوزارية للفتوى حول نازلة فيروس كورونا - ليازيدي سليمان; بن السايح محمد (University of Eloued جامعة الوادي, 2023)
تهدف هذه الدراسة إلى بيان أثر القواعد الفقهية في تأصيل الفتاوى التابعة لوزارة الشؤون الدينية والأوقاف الجزائرية المتعلقة بفيروس نازلة كورونا، من خلال تأصيل القواعد الفقهية الضابطة للمسائل والفروع المختلفة لفيروس نازلة كورونا الذي اجتاح العالم، والقواعد التي تناولها البحث بالدراسة، لها صلة مباشرة بالمسائل المترتبة على نازلة فيروس كورونا، وأهم النتائج التي تم التوصل إليها ما يلي: - أهمية دراسة الفتاوى الجماعية المعاصرة، لما يترتب عليها من تدريب عملي في كيفية ردِّ الفروع إلى أصولها، ومدى توظيف لجنة الفتوى للقواعد الفقهية في هذه الفتاوى. - أهم القواعد الفقهية التي اعتمدت عليها لجنة الفتوى التابعة لوزارة الشؤون الدينية والأوقاف الجزائرية، في إصدار الفتاوى، قاعدة لا ضرر ولا ضرار، وقاعدة المشقة تجلب التيسير. Abstract: This study aims to demonstrate the impact of the jurisprudential rules in rooting the fatwas of the Algerian Ministry of Religious Affairs and Endowments related to the Corona virus, through the rooting of the jurisprudential rules that control the issues and the various branches of the Corona virus that swept the world, and the rules that the research dealt with in the study are directly related to the issues arising from Corona virus, and the most important results that were reached are as follows: - The importance of studying contemporary collective fatwas, due to the practical training that results from them in how to return the branches to their origins, and the extent to which the Fatwa Committee employs the jurisprudential rules in these fatwas. -The most important jurisprudential rules on which the Fatwa Committee of the Algerian Ministry of Religious Affairs and Endowments relied in issuing fatwas, the rule of neither harm nor harm, and the rule of hardship brings facilitation
Keywords: الفتوى; تأصيل; اللجنة الوزارية; فيروس كورنا